Indicadores altmétricos da ciência brasileira: um estudo na Plataforma Lattes - Souza, Iara Vidal Pereira de (2019)
Altmetrics is a subarea of Scientometrics that studies the dissemination of scholarly articles in the social web, promising to capture impacts that are invisible to traditional scholarly metrics. This promise is particularly appealing to countries like Brazil, whose scholarly production is underrepresented in the international databases Web of Science and Scopus, currently the main data sources on the impact of sciente. In order to determine if and how Altmetrics can be useful to assess Brazilian science, it is necessary to understand its specific characteristics and biases. This PhD research is a descriptive study of Brazilian science’s repercussion in altmetric sources, using journal articles with a DOI that were recorded by PhD holders in the Lattes Platform and the sources monitored by the company Altmetric. We identify the sources and the knowledge areas where Brazilian science gathers more attention, and analyze the differences in volume and distribution of altmetric attention between open and closed access articles, and between articles indexed or not indexed in Web of Science and Scopus. Altmetric coverage of the articles in the sample is generally low, around 28%. Only 5 sources show coverage levels above 2%: Mendeley, Twitter, Facebook, news sites and blogs. Distribution of altmetric events among the DOIs in the sample is assimetric, with most articles gathering attention levels well below the average, and a few attracting fairly high levels of attention. Over 90% of the DOIs with at least 1 event registered by Altmetric are indexed in the Web of Science and/or in Scopus, suggesting that being present in these databases is still an important factor for the dissemination/popularity of Brazilian articles. Data is inconclusive concerning a possible altmetric advantage for open access articles. Among knowledge areas, Biological Sciences, Health Sciences and Humanities are the most promising for future altmetric studies.